Cybersecurity Threats and Mitigation Strategies in AI Applications (Journal of The Colloquium for Information Systems Security Education, 2025)
The integration of artificial intelligence (AI) into daily life and critical infrastructure has elevated the importance of addressing cybersecurity concerns within AI applications. While AI systems offer numerous benefits, such as enhanced efficiency, automation, and decision-making, they also introduce novel vulnerabilities and threats. Ensuring the security and reliability of these systems is crucial. This paper investigates key cybersecurity challenges associated with AI, including data privacy, integrity, adversarial attacks, and the ethical implications of AI in security. Additionally, it examines the role of Shapley Additive explainable AI in promoting transparency, allowing for greater interpretability of AI models and insights into decision-making processes.
Keywords: AI security; cybersecurity; cyber threats; generative AI; explainable AI; data privacy